IPWL (Instansi Penerima Wajib Lapor) Rehabilitasi Narkoba - Syahputra, Juli Raya; Singh, Simrenjit (Media Hukum Indonesia (MHI), 2025)
Prevention is better than cure, these words are very appropriate to describe narcotics. Narcotics are dangerous objects for anyone, so early prevention must be done so that drugs are not misused. For this reason, the Government has issued a policy of IPWL (Mandatory Reporting Receiving Agency) which is a step that is not only eradication, but also a process of rehabilitation of addicts in synergy with related agencies. However, many people still do not know about this policy, so the writing of this Scientific Journal aims to provide information for readers using the literature study research method.